PEMBERDAYAAN APARATUR SIPIL NEGARA DI BAGIAN HUKUM SEKRETARIAT DAERAH PROVINSI SULAWESI UTARA - PINGKAN TESALEONIKA PONTOH; FEMMY TULUSAN; NOVIE PALAR (Sam Ratulangi University, 2022)
ABSTRACTCivil servants have a decisive role, namely as thinkers, implementers, planners, and controllers of development.Thus, civil servants have a very important role in facilitating the running of the wheels of government and theimplementation of national development. The purpose of this study was to determine the empowerment of StateCivil Apparatus in the Legal Section of the Regional Secretariat of North Sulawesi Province. This study usesdescriptive qualitative research methods. Data collection techniques used are observation, interviews anddocumentation. In this research, the data analysis technique used is data analysis technique according to Milesand Huberman. The results of this study indicate the empowerment of state civil apparatus, namely theprocurement of employees who have followed the rules and regulations applied by the Regional Personnel Agencyof North Sulawesi Province, both career development and discipline application to all existing employees as wellas character, knowledge and skill development in performance development. organization, the three trainings andquick education carried out by the external party, the legal division of the regional secretariat of North SulawesiProvince. So it can be concluded that the empowerment of civil servants in empowering the State Civil Apparatusin the Legal Section of the Regional Secretariat of North Sulawesi Province is considered quite good in carryingout the programs and tasks that have been carried out.Keywords : Empowerment, State Civil Apparatus